Antibacterial properties of Persicaria minor (Huds.) ethanolic and aqueous-ethanolic leaf extracts - Musa Ahmed Abubakar, Razauden Mohamed Zulkifli, Wan Nur Atiqah Wan Hassan, Amir Husni Mohd Shariff, Nik Ahmad Nizam Nik Malek, Zarita Zakaria, Farediah Ahmad (Journal of Applied Pharmaceutical Science, 2015)
Persicaria minor known as small water-pepper is used traditionally for the treatment of dandruffs and stomach indigestion. Therefore, this study was designed to evaluate the antibacterial activity of plant leaf material. 30% aqueous-ethanol and 100% aqueous were used for solvent extraction. Both extracts were evaluated for total protein and polysaccharide contents and results were compared. The extracts were then tested against four strains of bacteria; Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 11229, Staphylococcus aureus ATCC 6538and Pseudomonas aeruginosa ATCC 1544,at different concentrations using disc-diffusion and microplate dilution assays with penicillin being used as a positive control standard. Both extracts showed antibacterial activity against S. aureus, E. faecalis, and E. coli, respectively with aqueous-ethanolic extract being more potent. However, none of the extracts were active against P. aeruginosa. Results from this study truly illustrated high potential of P. minor leaves to be used topically as antibacterial agent for controlling of tested colony.
Keywords: Antibacterial activity, Persicaria minor, protein, polysaccharide.